2005
DOI: 10.1159/000086437
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Factor Analysis for Plaque Psoriasis

Abstract: Background: Little is known about the long-term prognostic factors which affect clinical outcomes after the diagnosis of psoriasis. Objective: To identify the prognostic factors which predict long-term outcomes after diagnosis. Methods: Patients’ clinical characteristics at diagnosis were associated with long-term prognosis using the logistic regression method for 169 psoriasis patients (median follow-up time 11.6 years). Results: The factors age ≧40 [odds ratio 0.27, 95% confidence interval (CI) 0.10–0.72, p … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0
6

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 26 publications
3
26
0
6
Order By: Relevance
“…It is thought that obesity has a negative influence on the course of psoriasis [118], due to the increased synthesis of leptin, IL-6, TNF-alpha and reduced production of adiponectin by fat tissue [73]. A negative correlation between plasma IL-6 and adiponectin levels in obese patients has been observed [72].…”
Section: Interleukin-6 (Il-6)mentioning
confidence: 99%
“…It is thought that obesity has a negative influence on the course of psoriasis [118], due to the increased synthesis of leptin, IL-6, TNF-alpha and reduced production of adiponectin by fat tissue [73]. A negative correlation between plasma IL-6 and adiponectin levels in obese patients has been observed [72].…”
Section: Interleukin-6 (Il-6)mentioning
confidence: 99%
“…Psoriatic patients have a higher prevalence of overweight and obesity compared with non-psoriatic patients [28]. Overweight and obesity has different risk effect on severity and manifestations of psoriasis and might be useful for better evaluating psoriasis clinically (was statistically correlated with body mass index (BMI) (r = 0.184, P < 0.01) [28].Elevated BMI (>25) was significantly associated with long-term prognosis of psoriasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, strong association was observed between body mass index and psoriasis as indicated in this study. Sakai et al analyzed a cohort of 169 psoriasis patients over more than 10 years and found that elevated BMI >25 was significantly associated with long term prognosis of psoriasis [28]. Studies done in Sweden have also found a significant association between obesity and increased morbidity of psoriasis [29].…”
Section: Discussionmentioning
confidence: 99%
“…Ancak obezite cerrahisi sonrası psoriasis şiddetinde artış görüldüğüne dair çalışmalar da mevcuttur 32 . Yapılan birçok çalışma BMI'nın psoriasis prevalansı ve şiddeti ile korele olduğunu göstermiştir 5,33 . BMI arttıkça psoriasis riskinin arttığı öngörülmüş, mevcut psoriasisi olanlarda ise BMI>25 olması kötü prognostik faktörlerden biri olarak kabul edilmiştir 16,22,33 .…”
Section: Gi Riflunclassified
“…Yapılan birçok çalışma BMI'nın psoriasis prevalansı ve şiddeti ile korele olduğunu göstermiştir 5,33 . BMI arttıkça psoriasis riskinin arttığı öngörülmüş, mevcut psoriasisi olanlarda ise BMI>25 olması kötü prognostik faktörlerden biri olarak kabul edilmiştir 16,22,33 . Ayrıca obez psoriasis hastalarının normal kilodaki hastalara göre sistemik tedavilere özellikle de biyolojik tedavilere daha az cevap verdiği ve sistemik tedaviye bağlı hiperlipidemi, hepatotoksisite, nefrotoksisite gibi yan etkilerin bu hastalarda daha sık geliştiği gösterilmiştir 7,11,34 .…”
Section: Gi Riflunclassified